Legal Protection For Juvenile Offenders In The Criminal Justice Process (Comparative Study Of Islamic Law And Positive Law In Indonesia) - Ruchendi, Dudi (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN EKONOMI DAN HUKUM ISLAM), 2024)
This study aims to determine the rights of children who commit criminal offenses in the judicial and investigative processes in legal protection. The method used is the normative juridical and sociological juridical approach. The results of this study are as follows: first, the investigation process at the Polres is carried out by child investigators who are accompanied by parents/guardians, legal counsel, and Bapas. At the Polsek level, the investigation is carried out by investigators who usually conduct investigations on adults due to the need for more human resources. Legal counsel must accompany children who are still suspects. There is no intimidation during the investigation process; everything is done according to the investigation procedure for children. Second, children’s rights during the trial period are fulfilled and protected by judges and public prosecutors by the Law on Juvenile Justice System. The rights contained in Article 3 of Law No. 11/2012 have fully met the principles of legal protection consisting of 4 (four) principles: The child cannot fight alone, the best interests of the child, the life cycle approach, and cross-sectoral. Keywords: Protection, law, juvenile offenses